TGFβ links EBV to multisystem inflammatory syndrome in children - Carl Christoph Goetzke; Mona Massoud; Stefan Frischbutter; Gabriela Maria Guerra; Marta Ferreira-Gomes; Frederik Heinrich; Anne Sae Lim von Stuckrad; Sebastian Wisniewski; Jan Robin Licha; Marina Bondareva; Lisa Ehlers; Samira Khaldi-Plassart; et al. (Springer Science and Business Media LLC, 2025)
Abstract In a subset of children and adolescents, SARS-CoV-2 infection induces a severe acute hyperinflammatory shock1 termed multisystem inflammatory syndrome in children (MIS-C) at four to eight weeks after infection. MIS-C is characterized by a specific T cell expansion2 and systemic hyperinflammation3. The pathogenesis of MIS-C remains largely unknown. Here we show that acute MIS-C is characterized by impaired reactivation of virus-reactive memory T cells, which depends on increased serum levels of the cytokine TGFβ resembling those that occur during severe COVID-19 (refs. 4,5). This functional impairment in T cell reactivity is accompanied by the presence of TGFβ-response signatures in T cells, B cells and monocytes along with reduced antigen-presentation capabilities of monocytes, and can be reversed by blocking TGFβ. Furthermore, T cell receptor repertoires of patients with MIS-C exhibit expansion of T cells expressing TCRVβ21.3, resembling Epstein–Barr virus (EBV)-reactive T cell clones capable of eliminating EBV-infected B cells. Additionally, serum TGFβ in patients with MIS-C can trigger EBV reactivation, which is reversible with TGFβ blockade. Clinically, the TGFβ-induced defect in T cell reactivity correlates with a higher EBV seroprevalence in patients with MIS-C compared with age-matched controls, along with the occurrence of EBV reactivation. Our findings establish a connection between SARS-CoV-2 infection and COVID-19 sequelae in children, in which impaired T cell cytotoxicity triggered by TGFβ overproduction leads to EBV reactivation and subsequent hyperinflammation.
Keywords: adolescent; b-lymphocytes; child; child; preschool; covid-19; epstein-barr virus infections; female; herpesvirus 4; human; humans; immunologic memory; male; monocytes; pediatric multisystem inflammatory disease; covid-19 related; sars-cov-2; systemic inflammatory response syndrome; t-lymphocytes; transforming growth factor beta; virus activation; t lymphocyte receptor; transforming growth factor beta; transforming growth factor beta; cell component; covid-19; infectious disease; protein; serum; severe acute respiratory syndrome; virus; article; b lymphocyte; blood sampling; cell isolation; child; controlled study; coronavirus disease 2019; cytotoxicity; disease severity; dna extraction; epstein barr virus; flow cytometry; follow up; gene expression; gene set enrichment analysis; genotyping; haplotype; hek293t cell line; high throughput sequencing; human; human cell; hyperinflammation; memory t lymphocyte; monocyte; pediatric multisystem inflammatory syndrome; peripheral blood mononuclear cell; polymerase chain reaction; protein expression; public health service; real time polymerase chain reaction; seroprevalence; single cell rna seq; t lymphocyte; transcriptome sequencing; virus reactivation; virus reactive memory t cell; western blotting; adolescent; blood; complication; coronavirus disease 2019; epstein barr virus infection; female; immunological memory; immunology; male; metabolism; pathology; physiology; preschool child; severe acute respiratory syndrome coronavirus 2; systemic inflammatory response syndrome; virology; virus activation